Fishes of the world - Nelson, Joseph S. (John Wiley & sons, 1994)
Considered a classic guide to fish classification and identification, it is the only book which uses recent findings in arranging all major fish groups worldwide. Covers 445 families in which over 21,700 species of living fishes are recognized. Adopts a synthetic approach to classification and presents groups in evolutionary order. This edition updates all families to reflect progress and changes in the field.